Synthesis method of nano FAU molecular sieve with high specific surface area

Through supergravity-enhanced mass transfer technology, the nanosheet-shaped FAU molecular sieve with high specific surface area is directly synthesized without template agents and pore-forming agents, which solves the problems of environmental pollution, resource waste and insufficient catalytic performance in the prior art, and achieves efficient and economical nano FAU molecular sieve synthesis.

CN119528166APending Publication Date: 2025-02-28BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411864091.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing FAU molecular sieve synthesis methods require the use of template agents and pore-forming agents, which leads to environmental pollution, waste of resources and high synthesis costs, and the specific surface area and pore volume of nano FAU molecular sieve obtained are insufficient.

Method used

Using supergravity-enhanced mass transfer technology, nanosheet-shaped FAU molecular sieve with high specific surface area is directly synthesized through hydrothermal crystallization reaction without template agents and pore-forming agents.

Benefits of technology

The synthesis of nanosheet-shaped FAU molecular sieve with high specific surface area and rich pore volume has been achieved, which shortens the synthesis cycle and improves the crystallinity and catalytic performance. The method is green and economical and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528166A_ABST
    Figure CN119528166A_ABST
Patent Text Reader

Abstract

The invention discloses a high specific surface area nano FAU molecular sieve synthesis method, which comprises: 1) dissolving a silicon source, an aluminum source and an alkali source in water, and uniformly mixing in a premixing device to obtain a mixed solution A; standing and aging to obtain a guiding agent; 2) dissolving an alkali source and an aluminum source in water by taking a silicon source as a single material to obtain a mixed solution B; in premixing equipment, premixing a silicon source and the mixed solution B with the guiding agent prepared in the step 1) to form reaction initial gel; and 3) transferring the initial reaction gel in the premixing equipment into a crystallization kettle for hydrothermal crystallization reaction, taking out a product after the reaction is finished, filtering, washing and drying to obtain the FAU molecular sieve. The particle size of the nanosheet-shaped FAU molecular sieve is 20-450 nm, the specific surface area is 960-1100 m < 2 > / g, and the pore volume of mesopores is 0.1-0.8 cm < 3 > / g; more active sites can be provided, the diffusion path is shorter, and the molecular diffusivity can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve synthesis, and in particular relates to a method for synthesizing a nano FAU molecular sieve with a high specific surface area. Background Art

[0002] FAU molecular sieve with microporous structure is one of the most important active components of catalytic cracking catalyst. It is widely used in adsorption catalysis fields such as fine chemicals and petroleum processing due to its high specific surface area, good hydrothermal stability, adjustable acidity, pore size and surface properties. Although the synthesis process of FAU molecular sieve is relatively mature and widely used in industry, it still faces challenges in the optimization of molecular sieve synthesis path and structure, and the optimization of molecular sieve catalytic performance. The large number of regular microporous structures in FAU molecular sieve provide a large number of active sites for catalytic reactions, but the shape-selective FAU molecular sieve has pore restrictions, so that only reactant molecules with a kinetic diameter smaller than the pore size of the molecular sieve can enter the pores and contact the active sites to participate in chemical reactions, while reactant molecules larger than the pore size are not conducive to their reaction. In addition, the traditional FAU molecular sieve has an octahedral skeleton structure, the grain size generally ranges from a few hundred nanometers to a few microns, the pores are long, and the active centers are mostly distributed in the micropores, which makes the diffusion path limited and difficult to react, and even forms secondary reactions to deactivate the molecular sieve carbon deposition and shorten its service life. Therefore, how to design, construct and optimize the pore structure and diffusion path of molecular sieves is crucial to the overall catalyst performance.

[0003] Nano FAU molecular sieves show better catalytic activity, selectivity and catalytic life due to their small particle size, short diffusion path and high specific surface area, and the thinner the sheet-like morphology molecular sieve is considered to be an excellent catalyst in the fields of oil refining and petrochemicals (Nature, 2009, 461, 182-183). Therefore, the morphology of the molecular sieve will greatly affect the catalytic performance of the molecular sieve, and how to reasonably design the morphology of the molecular sieve is of great significance to the catalytic application of the molecular sieve. By reducing the size in the b-axis direction or the overall particle size, a sheet-like morphology FAU molecular sieve or a nano FAU molecular sieve with a short pore and a large surface area can be obtained, thereby effectively reducing the diffusion restriction problem in the reaction process, so the sheet FAU molecular sieve or the nano FAU molecular sieve has a catalytic ability superior to that of the conventional octahedral FAU molecular sieve (Ind. Eng. Chem. Res. 1999, 38, 1350-1356). At present, most of the synthesis methods of flaky FAU molecular sieves require the use of organic templates, macromolecular blocks or other inorganic additives, which not only pollute the environment, but also waste resources, increase the synthesis cost, and fail to obtain excellent structural properties. For example, patents CN110078093A, CN112723374A, CN115594193A, CN114074947A, and CN110627089A all synthesized flaky FAU molecular sieves, but the specific surface area of ​​the obtained FAU molecular sieves does not exceed 800m 2 / g, and some patents also need to add Zr2O4, block polymers (such as P123), PEG-600 (6000) or quaternary ammonium compounds, etc. In order to obtain mesoporous FAU molecular sieves, some patents add different pore-forming agents to form pores, which increases the cost of the system and is not easy to industrialize. Moreover, most of the currently synthesized nano FAU molecular sieves are granular, spherical or octahedral, and their diffusion path is inferior to the lamellar morphology. For example, patent CN101177281A uses ultra-gravity to synthesize nano FAU molecular sieves, but the synthesized molecular sieve is an octahedral morphology. The obtained nano FAU molecular sieve needs to be calcined, and its specific surface area is only 700m 2 In addition, CN114132944A, CN1238305A, CN1238306A, CN114426286A, CN1951566A, CN1785807A and CN106698460A all synthesized nano FAU molecular sieves of about 20-600nm, but they were not in sheet form and had a specific surface area of ​​400-800m 2 / g, and some patents also require additional additives such as macroporous carbon or rare earth ions. Therefore, it is of great significance to develop a high specific surface area nano-sheet FAU molecular sieve synthesis technology without templates or additives. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a method for synthesizing a nano FAU molecular sieve with a high specific surface area; the method of the present invention can not only directly synthesize a nano-sheet FAU molecular sieve with a high specific surface area in the absence of a template, but also utilizes ultra-gravity to enhance mass transfer to effectively shorten the aging time of the directing agent and the crystallization rate of the molecular sieve, thereby shortening the molecular sieve synthesis cycle.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0007] 1) dissolving a silicon source, an aluminum source and an alkali source in water, and uniformly mixing them in a premixing device to obtain a mixed solution A; allowing the solution to stand for aging to obtain a directing agent;

[0008] 2) taking the silicon source as a single material, dissolving the alkali source and the aluminum source in water to obtain a mixed solution B; in a premixing device, premixing the silicon source and the mixed solution B with the directing agent obtained in step 1) to form an initial reaction gel;

[0009] 3) The initial reaction gel in the premixing device is transferred to a crystallization kettle for hydrothermal crystallization reaction. After the reaction is completed, the product is taken out, filtered, washed, and dried to obtain the FAU molecular sieve.

[0010] Preferably, in step 1) and step 2), the silicon source is selected from one or more of water glass, silica sol, silica gel or white carbon black.

[0011] Preferably, in step 1) and step 2), the aluminum source is selected from one or more of aluminum hydroxide, aluminum sulfate, sodium aluminate, sodium metaaluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, and aluminum sol.

[0012] Preferably, in step 1) and step 2), the alkali source is selected from one or more of NaOH, KOH, LiOH and ammonia water.

[0013] Preferably, in step 1) and step 2), the premixing equipment is a supergravity reactor; the supergravity reactor reaction includes one of an internal circulation supergravity reactor, an external circulation supergravity reactor, and a supergravity dynamic crystallization integrated equipment.

[0014] Preferably, in step 1), the silicon source, aluminum source, alkali source and water are mixed in a molar ratio of 6-50 (in terms of SiO2): 1 (in terms of Al2O3): 5-45 (in terms of Na2O): 100-500 (H2O).

[0015] Preferably, in step 1), the temperature for uniform mixing in the premixing device is 0-100°C, preferably 20°C-40°C; and the static aging time is 0.1-100h, preferably 10-60h.

[0016] Preferably, in step 2), the amount of the directing agent added is 1 wt% to 50 wt% of the weight of the reaction system.

[0017] Preferably, in step 2), the temperature in the premixing device is 0-100°C, preferably 20°C-40°C; the premixing speed is 1-3000r / min, wherein: if a conventional stirred tank is used for premixing, the speed is 300-1000r / min; if a supergravity reactor is used for premixing, the speed is 1500-2850r / min.

[0018] Preferably, in step 3), the FAU molecular sieve has a particle size of 20-450 nm and a specific surface area of ​​800-1100 m 2 / g, mesopore volume 0.1-0.8cm 3 / g.

[0019] Preferably, in step 3), the crystallization temperature of the hydrothermal crystallization reaction is 70-150° C., preferably 90-110° C.; the crystallization time of the hydrothermal crystallization reaction is 5-48 h.

[0020] Preferably, in step 3), the washing is performed by washing with deionized water for 3-6 times; the drying is performed by drying in a forced air drying oven at a temperature of 60-120° C. for 6-12 hours.

[0021] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0022] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention utilizes ultra-gravity to intensify reaction and mass transfer and generate nano-micro bubbles, which can effectively promote the aging of the directing agent and the nucleation and crystallization of the FAU molecular sieve, shorten the aging time of the directing agent and the crystallization time of the molecular sieve, thereby shortening the entire synthesis cycle of the molecular sieve, and improving the crystallinity, specific surface area and mesopore volume of the molecular sieve. This method is of great significance to the industrial application of molecular sieves.

[0025] 2. The present invention utilizes ultra-gravity to enhance the synthesis of high specific surface area nano-sheet FAU molecular sieves by conventional directing agent hydrothermal synthesis under template-free conditions. No additional template agent, pore-forming agent or other additives are required to obtain nano-sheet FAU molecular sieves with rich specific surface area and pore volume. The synthesis process is green and economical, and has more prospects for the application of molecular sieves.

[0026] 3. The nano-sheet FAU molecular sieve synthesized by the present invention has a particle size of 20-450nm and a specific surface area of ​​960-1100m 2 / g, mesopore volume 0.1-0.8cm 3 / g; it has a higher specific surface area, can provide more active sites, and the flaky molecular sieve has a shorter diffusion path than the octahedral molecular sieve, which can improve the molecular diffusion capacity.

[0027] 4. The equipment used for the ultra-gravity enhanced synthesis of high specific surface area nano-sheet FAU molecular sieve provided by the present invention has the characteristics of small size and no amplification effect, and can be widely used in various fields such as catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0029] Figure 1 An experimental flow chart showing a method for synthesizing a nano FAU molecular sieve with a high specific surface area according to the present invention;

[0030] Figure 2 The SEM image of the sample prepared in Example 1 of the present invention is shown;

[0031] Figure 3 The SEM image of the sample prepared in Example 2 of the present invention is shown;

[0032] Figure 4 The SEM image of the sample prepared in Comparative Example 1 of the present invention is shown;

[0033] Figure 5 The N2 adsorption-desorption curves of the samples prepared in Example 1, Example 2 and Comparative Example 1 of the present invention are shown;

[0034] Figure 6 The pore size distribution curves of the samples prepared in Example 1, Example 2 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0035] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0036] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the field can be used. The materials, reagents, etc. used in the present invention can be obtained from commercial channels unless otherwise specified, and the equipment used in the present invention can be conventional equipment in the field or can be carried out with reference to the existing technology in the field.

[0037] As another aspect of the present invention, a method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0038] 1) dissolving a silicon source, an aluminum source and an alkali source in water, and uniformly mixing them in a premixing device to obtain a mixed solution A; allowing the solution to stand for aging to obtain a directing agent;

[0039] 2) taking the silicon source as a single material, dissolving the alkali source and the aluminum source in water to obtain a mixed solution B; in a premixing device, premixing the silicon source and the mixed solution B with the directing agent obtained in step 1) to form an initial reaction gel;

[0040] 3) The initial reaction gel in the premixing device is transferred to a crystallization kettle for hydrothermal crystallization reaction. After the reaction is completed, the product is taken out, filtered, washed, and dried to obtain the FAU molecular sieve.

[0041] According to some embodiments of the present invention, in step 1) and step 2), the silicon source is selected from one or more of water glass, silica sol, silica gel or white carbon black.

[0042] According to certain embodiments of the present invention, in step 1) and step 2), the aluminum source is selected from one or more of aluminum hydroxide, aluminum sulfate, sodium aluminate, sodium metaaluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, and aluminum sol.

[0043] According to some embodiments of the present invention, in step 1) and step 2), the alkali source is selected from one or more of NaOH, KOH, LiOH and ammonia water.

[0044] According to certain embodiments of the present invention, in step 1) and step 2), the premixing device is a supergravity reactor; the supergravity reactor reaction includes one of an internal circulation supergravity reactor, an external circulation supergravity reactor, and a supergravity dynamic crystallization integrated device. Supergravity technology is a means of strengthening reaction and mass transfer. The liquid is broken into droplets, liquid films and liquid lines by high-speed shear force, and the mixing and mass transfer process of materials is achieved from a microscopic point of view. The synthesis of molecular sieves mainly includes two stages: premixing and crystallization. Introducing supergravity technology into the premixing stage of molecular sieves can effectively improve the mass transfer efficiency of the reaction process, thereby increasing the crystallization rate of molecular sieves. Patents CN114870768A, CN114870663A and CN108217674A all confirm that the synthesis of molecular sieves using supergravity reactors can promote the continuous participation of the liquid phase in the reaction, thereby strengthening mass transfer, and supergravity reactors can produce nano-micro bubbles to promote reaction crystallization, and the obtained molecular sieve particle size is more uniform and narrow. Therefore, the introduction of ultra-gravity technology can improve the crystal quality and crystallization rate of molecular sieves and reduce the particle size distribution of crystals.

[0045] According to certain embodiments of the present invention, in step 1), the silicon source, aluminum source, alkali source and water are mixed in a molar ratio of 6-50 (in terms of SiO2): 1 (in terms of Al2O3): 5-45 (in terms of Na2O): 100-500 (H2O).

[0046] According to certain embodiments of the present invention, in step 1), the temperature of the uniform mixing in the premixing device is 0-100° C., preferably 20° C.-40° C.; and the static aging time is 0.1-100 h, preferably 10-60 h.

[0047] According to certain embodiments of the present invention, in step 2), the amount of the directing agent added is 1 wt%-50 wt% of the content of the molecular sieve reaction system.

[0048] According to certain embodiments of the present invention, in step 2), the temperature in the premixing device is 0-100°C, preferably 20°C-40°C; the premixing speed is 1-3000r / min, wherein: if a conventional stirred tank is used for premixing, the speed is 300-1000r / min; if a supergravity reactor is used for premixing, the speed is 1500-2850r / min.

[0049] According to certain embodiments of the present invention, in step 3), the FAU molecular sieve has a particle size of 20-450 nm and a specific surface area of ​​960-1100 m 2 / g, mesopore volume 0.1-0.8cm 3 / g.

[0050] According to some embodiments of the present invention, in step 3), the crystallization temperature of the hydrothermal crystallization reaction is 70-150° C., preferably 90-110° C.; and the crystallization time of the hydrothermal crystallization reaction is 5-48 h.

[0051] According to some embodiments of the present invention, in step 3), the washing is performed by washing with deionized water for 3-6 times; the drying is performed by drying in a forced air drying oven at a temperature of 60-120° C. for 6-12 hours.

[0052] Example 1

[0053] A method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0054] Preparation of the directing agent: Weigh 14.8 g of sodium hydroxide, 32.8 g of water and 2.44 g of aluminum hydroxide, mix and stir until completely dissolved to obtain a high-alkali sodium aluminate solution, then add the high-alkali sodium aluminate solution to 43.6 g of water glass solution (27 wt% SiO2), stir for 2 hours under normal stirring, and then age at 32°C for 14 hours to obtain a directing agent.

[0055] Preparation of initial reaction gel: 11.3g aluminum sulfate was dissolved in 137.6g water to form an aluminum sulfate solution; 20.9g sodium hydroxide, 66.5g water and 12.72g aluminum hydroxide were weighed and stirred until completely dissolved to form a low-alkali sodium aluminate solution. 185.2g water glass solution, 74.2g directing agent, 123g aluminum sulfate solution and 46.7g low-alkali sodium aluminate solution were pumped into a supergravity reactor and premixed and stirred for 15 minutes to obtain the initial reaction gel.

[0056] The initial reaction gel was transferred to an autoclave and crystallized for 24 hours at 100° C. After the crystallization was completed, the reacted material was taken out, filtered, washed, and dried to obtain a nano-sheet FAU molecular sieve with a high specific surface area.

[0057] The relative crystallinity of the nano-sheet FAU molecular sieve is 101.8%, the particle size of the FAU molecular sieve is 146.2nm, and the specific surface area is 1012.58m 2 / g, and the total pore volume is 0.63cm 3 / g, and the mesopore volume is 0.26cm 3 / g.

[0058] Example 2

[0059] A method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0060] Preparation of the guiding agent: Weigh 7.5g of sodium hydroxide, 16.6g of water and 0.9g of aluminum hydroxide, mix and stir until completely dissolved to obtain a high-alkali sodium aluminate solution, then add the high-alkali sodium aluminate solution to 23.2g of water glass solution (27wt% SiO2), stir for 2h under normal stirring, and then age at 32°C for 14h to obtain a guiding agent.

[0061] Preparation of initial reaction gel: 33.0g aluminum sulfate was dissolved in 49.0g water to form an aluminum sulfate solution; 9.0g sodium hydroxide, 51.2g water and 5.8g aluminum hydroxide were weighed and stirred until completely dissolved to form a low-alkali sodium aluminate solution. 120.4g water glass solution and the above-prepared directing agent, aluminum sulfate solution and low-alkali sodium aluminate solution were pumped into the supergravity reactor and pre-mixed and stirred for 10 minutes to obtain the initial reaction gel.

[0062] The initial reaction gel was transferred to an autoclave and crystallized for 24 hours at 100° C. After the crystallization was completed, the reacted material was taken out, filtered, washed, and dried to obtain a nano-sheet FAU molecular sieve with a high specific surface area.

[0063] After testing, the relative crystallinity of the nano-sheet FAU molecular sieve prepared in this embodiment is 108.9%, the particle size of the FAU molecular sieve is 231.51nm, and the specific surface area is 1078.52m 2 / g, with a total pore volume of 0.60 cm 3 / g, and the mesopore volume is 0.19 cm 3 / g.

[0064] Example 3

[0065] A method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0066] Preparation of the guiding agent: Weigh 29.5g of sodium hydroxide, 65.68g of water and 4.88g of aluminum hydroxide, mix and stir until completely dissolved to obtain a high-alkali sodium aluminate solution, weigh 87.2g of water glass solution (27wt% SiO2) and pump it into a supergravity reactor, then pump the high-alkali sodium aluminate solution into the supergravity reactor and premix it with the water glass for 5 minutes, then place it at 32°C and age it for 8 hours to obtain a guiding agent.

[0067] Preparation of initial reaction gel: 11.3g aluminum sulfate was dissolved in 137.6g water to form an aluminum sulfate solution; 20.9g sodium hydroxide, 66.5g water and 12.72g aluminum hydroxide were weighed and stirred until completely dissolved to form a low-alkali sodium aluminate solution. 185.2g water glass solution, 74.2g directing agent, 123g aluminum sulfate solution and 46.7g low-alkali sodium aluminate solution were pumped into a supergravity reactor and premixed and stirred for 5 minutes to obtain the initial reaction gel.

[0068] The initial reaction gel was transferred to an autoclave and crystallized for 24 hours at 100° C. After the crystallization was completed, the reacted material was taken out, filtered, washed, and dried to obtain a nano-sheet FAU molecular sieve with a high specific surface area.

[0069] After testing, the relative crystallinity of the nano-sheet FAU molecular sieve prepared in this embodiment is 95.4%, the particle size of the FAU molecular sieve is 197.9 nm, and the specific surface area is 968.09 m 2 / g, and the total pore volume is 0.58 cm 3 / g, and the mesopore volume is 0.23cm 3 / g.

[0070] Example 4

[0071] A method for synthesizing a nano FAU molecular sieve with a high specific surface area comprises the following steps:

[0072] Preparation of the guiding agent: Weigh 29.5g of sodium hydroxide, 65.68g of water and 4.88g of aluminum hydroxide, mix and stir until completely dissolved to obtain a high-alkali sodium aluminate solution, weigh 87.2g of water glass solution (27wt% SiO2) and pump it into a supergravity reactor, then pump the high-alkali sodium aluminate solution into the supergravity reactor and premix it with the water glass for 30 minutes, then place it at 32°C and age it for 6 hours to obtain a guiding agent;

[0073] Preparation of the initial reaction gel: dissolve 11.3 g of aluminum sulfate in 137.6 g of water to form an aluminum sulfate solution; weigh 20.9 g of sodium hydroxide, 66.5 g of water and 12.72 g of aluminum hydroxide and stir until completely dissolved to form a low-alkali sodium aluminate solution; pump 185.2 g of water glass solution, 74.2 g of directing agent, 123 g of aluminum sulfate solution and 46.7 g of low-alkali sodium aluminate solution into an ultragravity reactor and premix and stir for 15 minutes to obtain the initial reaction gel.

[0074] The initial reaction gel was transferred to an autoclave and crystallized at 100° C. for 24 hours. After the crystallization was completed, the reacted material was taken out, filtered, washed, and dried to obtain a nano-sheet FAU molecular sieve with a high specific surface area.

[0075] After testing, the relative crystallinity of the nano-sheet FAU molecular sieve prepared in this embodiment is 100.2%, the particle size of the FAU molecular sieve is 137.5nm, and the specific surface area is 1001.2m 2 / g, with a total pore volume of 0.60 cm 3 / g, mesopore volume is 0.25cm 3 / g.

[0076] Comparative Example 1

[0077] Example 1 was repeated, except that the ultra-gravity reactor used in the initial gel preparation process was replaced with a conventional stirred tank, and after all the raw materials were added in the initial gel preparation stage, the reaction was stirred for 3 hours, and then transferred to a hydrothermal crystallization tank for crystallization at 100°C for 24 hours. After the same filtration, washing and drying, a nano-sheet FAU molecular sieve was obtained, and the particle size distribution of the FAU molecular sieve was mostly concentrated around 190nm, the crystallinity was 100%, and the specific surface area was 843.07m 2 / g, with a total pore volume of 0.50 cm 3 / g, and the mesopore volume is 0.18cm 3 / g.

[0078] It can be seen that the use of traditional stirred tank premixing in the premixing stage limits the mass transfer and dispersion of the system materials, resulting in low crystallinity of the product, large particle size, greatly reduced specific surface area, and small mesopore volume.

[0079] Comparative Example 2

[0080] A method for preparing nano FAU molecular sieve comprises the following steps:

[0081] Preparation of the guiding agent: 725 ml of 0.88 mol / L sodium silicate solution and 100 ml of 0.91 mol / L sodium aluminate solution were pumped into an ultra-gravity reactor for premixing to form a mixed solution with a silicon-aluminum ratio of 7:1. The solution was aged at 32°C for 24 hours to obtain a guiding agent.

[0082] Preparation of the initial reaction gel: 4250 ml of 0.75 mol / L sodium silicate and 1300 ml of 1.21 mol / L sodium aluminate were pumped into an ultra-gravity reactor for premixing to form a mother liquor with a silicon-aluminum ratio of 4:1, and the prepared mother liquor and the directing agent were premixed in an ultra-gravity reactor to form an initial reaction gel, which was then sealed and aged at room temperature for 24 hours.

[0083] The aged initial reaction gel was transferred to a crystallization reactor and crystallized for 12 hours at 100° C. After the crystallization, the reacted material was taken out, filtered, washed to a pH value of 7-9, and then dried; and calcined at 600° C. for 3 hours to form a nano FAU molecular sieve.

[0084] The FAU molecular sieve has an octahedral morphology and a relative crystallinity of 96.2%. The particle size of the FAU molecular sieve is about 200 nm and the specific surface area is 735 m 2 / g.

[0085] It can be seen that although the same guiding agent method is used to pre-mix the nano FAU molecular sieve under ultra-gravity, the growth rate and growth direction of the product are different due to the different formula proportions, so the morphology of the obtained molecular sieve is also inconsistent. In addition, the molecular sieve obtained by this formula has a lower specific surface area.

[0086] Comparative Example 3

[0087] A method for preparing nano FAU molecular sieve comprises the following steps:

[0088] Weigh 12.1g NaOH and 8.1g NaAlO2 and dissolve them in 143.9g H2O to form an aluminum source to wait for feeding; weigh 60.1g silica sol and the aluminum source and pump them into the ultra-gravity reactor at the same time. After premixing for 40 minutes, transfer the resulting initial reaction gel into a hydrothermal crystallization kettle and crystallize at 100°C for 24 hours. After filtering, washing and drying, the FAU molecular sieve is obtained. The FAU molecular sieve has an octahedral morphology, the particle size distribution is mostly concentrated around 2.8μm, the crystallinity is 120.2%, and the specific surface area is 806m 2 / g.

[0089] It can be seen that this method uses a non-directing agent hydrothermal method to synthesize FAU zeolite, but the different ratios of elements in the system lead to different nucleation and growth rates during the crystallization process, which in turn causes the zeolite synthesis to tend to grow in a typical octahedral morphology, and the zeolite synthesized by this method has a low specific surface area.

[0090] It can be seen from the examples and comparative examples that when the FAU molecular sieve is synthesized by the hydrothermal method using a directing agent, the introduction of supergravity can increase the crystallinity of the molecular sieve, reduce the particle size distribution, and increase the specific surface area. Comparative Example 2 is a current conventional synthesis scheme. Although the introduction of supergravity can obtain a FAU molecular sieve with a uniform particle size distribution, the molecular sieve obtained is an octahedral morphology, and the specific surface area is smaller than that of the present invention. In summary, the molecular sieve obtained by the preparation method of the supergravity-enhanced synthesis of FAU molecular sieve provided by the present invention has the characteristics of a nano-sheet structure with high crystallinity, high specific surface area and rich pore volume, and the synthesis process is green and economical, and has a broader application prospect.

[0091] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for synthesizing a nano FAU molecular sieve with a high specific surface area, characterized in that: The steps include: 1) dissolving a silicon source, an aluminum source and an alkali source in water, and uniformly mixing them in a premixing device to obtain a mixed solution A; allowing the solution to stand for aging to obtain a directing agent; 2) taking the silicon source as a single material, dissolving the alkali source and the aluminum source in water to obtain a mixed solution B; in a premixing device, premixing the silicon source and the mixed solution B with the directing agent obtained in step 1) to form an initial reaction gel; 3) The initial reaction gel in the premixing device is transferred to a crystallization kettle for hydrothermal crystallization reaction. After the reaction is completed, the product is taken out, filtered, washed, and dried to obtain the FAU molecular sieve.

2. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1) and step 2), the silicon source is selected from one or more of water glass, silica sol, silica gel or white carbon black.

3. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1) and step 2), the aluminum source is selected from one or more of aluminum hydroxide, aluminum sulfate, sodium aluminate, sodium metaaluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, and aluminum sol.

4. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1) and step 2), the alkali source is selected from one or more of NaOH, KOH, LiOH and ammonia water.

5. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1) and step 2), the premixing equipment is a supergravity reactor; the supergravity reactor reaction includes one of an internal circulation supergravity reactor, an external circulation supergravity reactor, and a supergravity dynamic crystallization integrated reactor.

6. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1), the silicon source, aluminum source, alkali source and water are mixed in a molar ratio of 6-50 (in terms of SiO2): 1 (in terms of Al2O3): 5-45 (in terms of Na2O): 100-500 (H2O).

7. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 1), the temperature for uniform mixing in the premixing device is 0-100° C., preferably 20° C.-40° C.; the static aging time is 0.1-100 h, preferably 10-60 h.

8. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 2), the amount of the directing agent added is 1 wt% to 50 wt% of the total weight of the reaction system.

9. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 2), the temperature in the premixing device is 0-100°C, preferably 20°C-40°C; the premixing speed is 1-3000r / min, wherein: if a common stirred tank is used for premixing, the speed is 300-1000r / min; if a supergravity reactor is used for premixing, the speed is 1500-2850r / min.

10. The method of producing high specific surface area nano-sheet FAU molecular sieve according to claim 1, characterized in that: In step 3), the FAU molecular sieve has a particle size of 20-450 nm and a specific surface area of ​​800-1100 m 2 / g, mesopore volume 0.1-0.8cm 3 / g; Preferably, in step 3), the crystallization temperature of the hydrothermal crystallization reaction is 70-150° C.; the crystallization time of the hydrothermal crystallization reaction is 5-48 h; Preferably, in step 3), the washing is performed by washing with deionized water for 3-6 times; the drying is performed by drying in a forced air drying oven at a temperature of 60-120° C. for 6-12 hours.

Citation Information

Patent Citations

  • Preparation method of small-grain NaY type molecular sieve

    CN111087001A

  • Molecular sieve morphology regulation and control method

    CN112678844A

  • Nano sheet Y molecular sieve aggregate as well as preparation method and application thereof

    CN114074947A